FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Apriadita Khusnul Fatimah (2023)
The purpose of this research is to obtain an empirical evidence of financial distress, fraudulent financial reporting, profitability have an influence on firm value with managerial ownership and institutional ownership as a moderating variable. This research data consist of 17 companies in healthcare secrot which listed on Indonesian Stock Exchange (IDX) for five years with the period of 2017 to 2021. Sample selected using total sampling method. Method of data analisis in this study using hypothesis method with moderate regression analysis. The result showed that capital fraudulent financial reporting has a significant effect toward firm value in a negative direction. While financial distress and profitability do not have a significant effect on firm value. Managerial ownership and institutional ownership can weaken influence of fraudulent financial reporting toward firm value, moreover managerial ownership and institutional ownership can not strengthen the effect of profitability toward firm value.